Review of Satellite based Internet of Things and Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The world has been witnessing a significant growth in the field of Internet of Things (IoT), associated technologies and applications. This emerging technology promises solutions to several existing and futuristic applications. These smart objects having their own ‘identity’ can communicate in large numbers over the network for multiple applications. Different geographical locations are covered with different levels of IoT sensors. For a much wider and global coverage, where the topographical complexities are very high, and access is difficult, space-based platforms are extremely useful. This paper reviews some of the works on use of satellites for Internet of things (SIoT) for delay sensitive and delay tolerant applications. The advantages of Low Earth Orbit (LEO) satellites over the Geostationary Earth Orbit (GEO) satellites and usefulness of LEO satellite constellations supplemented with terrestrial communication networks are discussed. Several applications including mission critical and military applications are also covered.